2016
DOI: 10.1007/s13246-016-0442-1
|View full text |Cite
|
Sign up to set email alerts
|

Effective management of patients with acute ischemic stroke based on lean production on thrombolytic flow optimization

Abstract: The efficacy of thrombolytic therapy for acute ischemic stroke (AIS) decreases when the administration of tissue plasminogen activator (tPA) is delayed. Derived from Toyota Production System, lean production aims to create top-quality products with high-efficiency procedures, a concept that easily applies to emergency medicine. In this study, we aimed to determine whether applying lean principles to flow optimization could hasten the initiation of thrombolysis. A multidisciplinary team (Stroke Team) was organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 37 publications
0
31
1
Order By: Relevance
“…8 Meanwhile, a second study saw significantly decreased median DTN times to 47 minutes, after the treatment process was enhanced by borrowing relevant principles from the automotive industry. 9 Although the achieved median DTN times in these studies were nearly 20 minutes longer than what was observed in the current study, they are a testament to the ability of process improvements to significantly decrease treatment times in acute stroke care.…”
Section: Discussioncontrasting
confidence: 48%
“…8 Meanwhile, a second study saw significantly decreased median DTN times to 47 minutes, after the treatment process was enhanced by borrowing relevant principles from the automotive industry. 9 Although the achieved median DTN times in these studies were nearly 20 minutes longer than what was observed in the current study, they are a testament to the ability of process improvements to significantly decrease treatment times in acute stroke care.…”
Section: Discussioncontrasting
confidence: 48%
“…Indeed, strategic efforts to improve individual aspects of stroke systems of care have yielded meaningful gains in overall outcomes. 6, 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…In the process of individualized sedation, it is necessary to choose a reasonable medication scheme and dosage under the doctor's instructions for different individuals, and the nerve physician who qualifies for the prescription of anesthetic and the ability of intubation and ventilation should participate in the supervision. In this research, the medical cooperation was good, and the time from entry into the operating room to recanalization in both groups was lower than the reference level reported in the literature [12][13][14]. Meanwhile, the incidence of adverse reactions was low and there was no intraoperative death.…”
Section: Individualized Sedation and Medication Schemementioning
confidence: 47%